Edukasi Bioteknologi Aedes Ber-Wolbachia Dalam Penanggulangan Demam Berdarah Dengue: Kajian Hukum Kesehatan di Kelurahan Gajahan Solo - Dahlan Sitohang; Hari Saktiningsih (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Cases of dengue fever (DBD) in Solo, including in Gajahan Village, have increased quite significantly. Until the beginning of the year, there were 1,010 cases of DBD recorded throughout Central Java, with 34 cases resulting in death. The purpose of this Community Service Priority problems in this caseconsist of two aspects, including health, law, Health problems include how the community can prevent the spread of Dengue Fever (DBD). While in terms of Law, it discusses community protection related to Aedes Biotechnology with Wolbachia in Handling Dengue Fever. The method of implementing the community service with a pre-test, then the presentation of material on